2016
DOI: 10.1021/acs.bioconjchem.6b00552
|View full text |Cite
|
Sign up to set email alerts
|

Novel 99mTc(III) Complexes [99mTcCl(CDO)(CDOH)2B–R] (CDOH2 = Cyclohexanedione Dioxime) Useful as Radiotracers for Heart Imaging

Abstract: In this study, we evaluated seven new Tc(III) complexes [TcCl(CDO)(CDOH)B-R] (Tc-2Fboroxime: R = 2-formylfuran-3-yl (2F); Tc-3Fboroxime: R = furan-3-yl (3F);Tc-5Fboroxime: R = 5-formyfuran-2-yl (5F); Tc-HPboroxime: R = 6-hydroxylpyridin-2-yl (HP);Tc-MPYboroxime: R = 5-methoxypyridin-3-yl (MPY); Tc-PMboroxime: R = 1,5-pyrimidin-3-yl (PM); andTc-4PYboroxime: R = pyridin-4-yl (4PY)) for their potential as heart imaging agents. All new Tc(III) radiotracers exceptTc-2Fboroxime were prepared with high radiochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Indeed, SPECT MPI using 99m Tc-radiopharmaceuticals is still the most common, non-invasive imaging tool for risk stratification of patients with CAD. In this regard, CZT-based cardiac SPECT cameras provide the potential for a superior spatial, temporal and energy resolution than conventional sodium iodine-based ones, encouraging the use of simultaneous dual or multiple radionuclide studies, and afford the reduction of the acquisition time and lower radiation dose. This is paralleled by the development of several new 99m Tc-based compounds for heart imaging designed to produce MPIAs having pharmacokinetic profiles approaching the criteria for an ideal perfusion tracer. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, SPECT MPI using 99m Tc-radiopharmaceuticals is still the most common, non-invasive imaging tool for risk stratification of patients with CAD. In this regard, CZT-based cardiac SPECT cameras provide the potential for a superior spatial, temporal and energy resolution than conventional sodium iodine-based ones, encouraging the use of simultaneous dual or multiple radionuclide studies, and afford the reduction of the acquisition time and lower radiation dose. This is paralleled by the development of several new 99m Tc-based compounds for heart imaging designed to produce MPIAs having pharmacokinetic profiles approaching the criteria for an ideal perfusion tracer. , …”
Section: Introductionmentioning
confidence: 99%
“…Various monocationic MPIAs, characterized by the presence of the [ 99m Tc]­[Tc­(N)­(PNP n )]-scaffold (PNP n = bisphosphinoamine) have been reported. For all these compounds, planar imaging of rats show early myocardial imaging without interference from nearby organ activity (lung and liver), which allows high quality of the myocardial imaging along with a clinically significant reduction in imaging delay. Among the tested compounds, [ 99m Tc]­[Tc­(N)­(DBODC)­(PNP5)] + ([DBODC = bis­( N -ethoxyethyl)-dithiocarbamate; PNP5 = bis­(dimethoxypropylphosphinoethyl)-ethoxyethylamine]), named [ 99m Tc]­TcN-DBODC­(5), displayed the most appropriate molecular features for the practical use in heart imaging, with an uptake mechanism and a pharmacokinetic behavior identical to those of the commercially available MPIAs [ 99m Tc]­Tc-sestamibi ([ 99m Tc]­Tc-MIBI) and [ 99m Tc]­Tc-tetrofosmin ([ 99m Tc]­Tc-Tf). Although its good pharmacokinetics, which allows higher imaging quality and superior clinical value for the detection of CAD over [ 99m Tc]­Tc-MIBI, its clinical properties seem close to those observed for [ 99m Tc]­Tc-Tf, failing to fully reproduce the encouraging experimental results achieved in preclinical studies. ,, This suggests that the three MPIAs possess similar clinical properties in terms of sensitivity, specificity, and diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies about milk proteins labeled with a radionuclide in the literature. One of them is about combining of radiolabeled whey proteins into casein micelles by heat processing published by Noh and Richardson [19][20][21][22][23][24][25][26][27][28][29]. In this study, WH was labeled with 14 C then radioactivities of the WH and radioacti-vities of the washed casein pellets from renneted skim milk were measured.…”
Section: Resultsmentioning
confidence: 99%
“…99m Tc-4ASboroxime was prepared using a kit formulation (Figure ). Heating at 100 °C is required in order to complete radiosynthesis. Its radiochemical purity (RCP) was >95% under the experimental conditions used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We have been interested in 99m Tc­(III) complexes [ 99m TcCl­(CDO)­(CDOH) 2 B-R] (Figure : CDOH 2 = cyclohexanedione dioxime; R = alkyl or aryl groups) as radiotracers for heart imaging. Recently, we found that the complex [ 99m TcCl­(CDO)­(CDOH) 2 B-4S] (Figure : 99m Tc-4Sboroxime, 4S-B­(OH) 2 = 4-(methanesulfonyl)­phenylboronic acid) is an excellent heart imaging agent . However, its liver uptake is high .…”
Section: Introductionmentioning
confidence: 99%